Activity-based anorexia during adolescence disrupts normal development of the CA1 pyramidal cells in the ventral hippocampus of female rats - Chowdhury, Tara G. (Hippocampus, 2014)
Anorexia nervosa (AN) is a psychiatric illness characterized by restricted eating and irrational fears of gaining weight. There is no accepted pharmacological treatment for AN, and AN has the highest mortality rate among psychiatric illnesses. Anorexia nervosa most commonly affects females during adolescence, suggesting an effect of sex and hormones on vulnerability to the disease. Activity-based anorexia (ABA) is a rodent model of AN that shares symptoms with AN, including over-exercise, elevation of stress hormones, and genetic links to anxiety traits. We previously reported that ABA in adolescent female rats results in increased apical dendritic branching in CA1 pyramidal cells of the ventral hippocampus at postnatal day 44 (P44). To examine the long-term effects of adolescent ABA (P44) in female rats, we compared the apical branching in the ventral hippocampal CA1 after recovery from ABA (P51) and after a relapse of ABA (P55) with age-matched controls. To examine the age-dependence of the hippocampal plasticity, we examined the effect of ABA during adulthood (P67). We found that while ABA at P44 resulted in increased branching of ventral hippocampal pyramidal cells, relapse of ABA at P55 resulted in decreased branching. Activity-based anorexia induced during adulthood did not have an effect on dendritic branching, suggesting an age-dependence of the vulnerability to structural plasticity. Cells from control animals were found to exhibit a dramatic increase in branching, more than doubling from P44 to P51, followed by pruning from P51 to P55. The proportion of mature spines on dendrites from the P44-ABA animals is similar to that on dendrites from P55-CON animals. These results suggest that the experience of ABA may cause precocious anatomical development of the ventral hippocampus. Importantly, we found that adolescence is a period of continued development of the hippocampus, and increased vulnerability to mental disorders during adolescence may be due to insults during this developmentally critical period.